Calcaneal Osteotomy Safe Zone to Prevent Neurological Damage: Fact or Fiction?. Issue 1 (February 2019) - Wills, Bradley; Lee, Sung Ro; Hudson, Parke William; SahraNavard, Bahman; de Cesar Netto, Cesar; Naranje, Sameer; Shah, Ashish
Background . Calcaneal osteotomy is a commonly used surgical option for the correction of hindfoot malalignment. A previous cadaveric study described a neurological "safe zone" for calcaneal osteotomy. We performed a retrospective chart review to evaluate the presence of neurological injuries following calcaneal osteotomies and the location of the osteotomy in relation to the reported safe zone. Methods . In this retrospective study, we reviewed charts of patients who underwent calcaneal osteotomy at our institution from 2011 to 2015. All immediate postoperative radiographs were examined and the shortest distance between the calcaneal osteotomy line and a reference line connecting the posterior superior apex of the calcaneal tuberosity to the origin of the plantar fascia was measured. If the osteotomy line was positioned within an area 11.2 mm anterior to the reference line, it was considered to be inside the neurological safe zone. We correlated the positioning of the osteotomy with the presence of postoperative neurological complications. Results . We identified 179 calcaneal osteotomy cases. Of the 174 (97.2%) nerve injury-free cases, 62.6% (109/174) were performed inside the defined "safe zone" while 37.4% (65/174) outside. A total of 5 (2.8%) nerve complications were identified: 3 (60%) were inside the safe zone and 2 (40%) outside the safe zone. Osteotomies outside the safe zone had a 1.114 relative risk of nerve injury with a 95% CI of 0.191 to 6.500 and showed no statistically significant difference ( P = .9042). Conclusion . Our findings suggest that the clinical "safe zone" in calcaneal osteotomies may not actually exist, likely because of wide anatomical variation of the implicated nerves, as described in prior studies. Patients should be properly counseled preoperatively on the low, but seemingly fixed, risk of nerve injury before undergoing calcaneal osteotomy. Levels of Evidence: Level III: Retrospective comparative study